NEW REALITIES ON THE OIL MARKET AND RUSSIA’S ENERGY POLICY - TOMBERG, Igor (CENTRAL ASIA AND THE CAUCASUS, 2004)
The current developments on the oil markets are evidence of not only a radically changing price context but of a novel situation in this vitally important sphere. Regrettably, the motto of Russian officials and the media: “Strike while the iron is hot” has nothing in common with a profound and professional analysis of what is going on.